Review of: Anthony Molho, Ετεροδοξία, Πειθάρχηση, Απόκρυψη στις απαρχές των Νεοτέρων χρόνων. Αναστοχασμοι για μια ευρωπαϊκη παραδοση / Dissent, Discipline, Dissimulation in Early Modern Europe: Reflections on a European Tradition, - Tagliaferri, Viviana (The Historical Review/La Revue Historique, 2017)
The present volume is the reworked text of the 2013 Annual C. Th. Dimaras Lecture given at the National Hellenic Research Foundation by Anthony Molho on the interplay of the historiographical triptych of dissent/ discipline/dissimulation. In particular, the book deals with the theme of dissimulation that the author developed in the narrative of the lecture, giving first its definition and then configuring it as a spread of European practice. He analyses its forms through the exposition of six case studies and concludes with several considerations on the ethic nature of dissimulation in a mass society in which privacy seems to have lost its value.